Functional Group‐Driven Competing Mechanism in Electrochemical Reaction and Adsorption/Desorption Processes toward High‐Capacity Aluminum‐Porphyrin Batteries - Jiao, Shuqiang; Han, Xue; Jiang, Li‐Li; Du, Xueyan; Huang, Zheng; Li, Shijie; Wang, Wei; Wang, Mingyong; Liu, Yunpeng; Song, Wei‐Li (Angewandte Chemie International Edition, 2024)
Nonaqueous organic aluminum batteries are considered as promising high‐safety energy storage devices due to stable ionic liquid electrolytes and Al metals. However, the stability and capacity of organic positive electrodes are limited by their inherent high solubility and low active organic molecules. To address such issues, here porphyrin compounds with rigid molecular structures present stable and reversible capability in electrochemically storing AlCl2+. Comparison between the porphyrin molecules with electron‐donating groups (TPP‐EDG) and with electron‐withdrawing groups (TPP‐EWG) suggests that EDG is responsible for increasing both highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energy levels, resulting in decreased redox potentials. On the other hand, EWG is associated with decreasing both HOMO and LUMO energy levels, leading to promoted redox potentials. EDG and EWG play critical roles in regulating electron density of porphyrin π bond and electrochemical energy storage kinetics behavior. The competitive mechanism between electrochemical redox reaction and de/adsorption processes suggests that TPP‐OCH3 delivers the highest specific capacity ~171.8 mAh g−1, approaching a record in the organic Al batteries. Porphyrin derivatives introduced by electron‐donating groups (EDG) and electron‐withdrawing groups (EWG) present the effect of functional groups on varying the electronic structure of porphyrin derivatives, which changes the redox potential and electrochemical energy storage performance. EWG can increase redox potential, while EDG reduces the redox potential. Due to the increasing electron density, EDG can improve Faradaic electrochemical reaction and de/adsorption capacitance contribution of porphyrin macrocycle, which is beneficial to improve the energy storage.